Claudin‐15 forms a water channel through the tight junction with distinct function compared to claudin‐2. (8th July 2019) - Rosenthal, Rita; Günzel, Dorothee; Piontek, Jörg; Krug, Susanne M.; Ayala‐Torres, Carlos; Hempel, Caroline; Theune, Dian; Fromm, Michael
Abstract: Aim: Claudin‐15 is mainly expressed in the small intestine and indirectly involved in glucose absorption. Similar to claudin‐2 and ‐10b, claudin‐15 is known to form a paracellular channel for small cations. Claudin‐2, but not claudin‐10b, also forms water channels. Here we experimentally tested whether claudin‐15 also mediates water transport and if yes, whether water transport is Na + ‐coupled, as seen for claudin‐2. Methods: MDCK C7 cells were stably transfected with claudin‐15. Ion and water permeability were investigated in confluent monolayers of control and claudin‐15‐expressing cells. Water flux was induced by an osmotic or ionic gradient. Results: Expression of claudin‐15 in MDCK cells strongly increased cation permeability. The permeability ratios for monovalent cations indicated a passage of partially hydrated ions through the claudin‐15 pore. Accordingly, its pore diameter was determined to be larger than that of claudin‐2 and claudin‐10b. Mannitol‐induced water flux was elevated in claudin‐15‐expressing cells compared to control cells. In contrast to the Na + ‐coupled water flux of claudin‐2 channels, claudin‐15‐mediated water flux was inhibited by Na + flux. Consequently, water flux was increased in Na + ‐free solution. Likewise, Na + flux was decreased after induction of water flux through claudin‐15. Conclusion: Claudin‐15, similar to claudin‐2, forms a paracellular cation and water channel. In functional contrast to claudin‐2, water and Na + fluxes through claudin‐15 inhibit each other. Claudin‐15 allows Na + to retain part of its hydration shell within the pore. This then reduces the simultaneous passage of additional water through the pore.